Intense Noxious Stimulus during an Adequate Depth of General Anesthesia Produces a Transient Burst Suppression Pattern in a Density Spectral Array - Ramamani Mariappan; James T. Magar (Journal of Neuroanaesthesiology and Critical Care)
There has been renewed interest in utilizing electroencephalogram (EEG)/processed EEG to assess the response to noxious stimuli under general anesthesia (GA). We are submitting multiple observations that explore the intriguing phenomenon of the transient burst suppression pattern (BSP) in the density spectral array (DSA) of the SedLine Masimo during intense noxious stimulation under GA. Three patients underwent spine surgery under sevoflurane/total intravenous anesthesia with adequate depth. Sudden transient BSP was noted on the DSA during an intense noxious stimulus. Traditionally, BSP on the processed EEG/DSA under GA in a hemodynamically stable patient indicates excessive hypnosis. It is usually treated by reducing the dose of a hypnotic agent. Decreasing the depth of anesthesia (DOA) in the presence of intense pain can have adverse consequences, especially in high-risk patients. Awareness of processed EEG/DSA changes associated with intense noxious stimuli, helps the anesthesiologist to titrate analgesia without altering DOA.